Wireless Mesh Network for Smart Farming - Gaikwad, Vijay; Shewale, Sakshi; Shikalkar, Asif; Shilimkar, Avanish; Solanke, Kuldip; Pawar, Swapnil (2023 2nd International Conference on Vision Towards Emerging Trends in Communication and Networking Technologies (ViTECoN), 2023)
Nearly every sector can be improved thanks to the Internet of Things (IoT). IoT in agriculture is fundamentally altering the way the world thinks about agriculture in addition to offering solutions to frequently timeconsuming and tiresome jobs. One of the foremost subjects in the area of communication engineering currently is the Internet of Things. But, when we talk about networking in the IoT world, wireless mesh networks are a network design that has been discussed for a long time but hasn't been widely adopted and can make a difference. For smart agriculture in this article, a mesh networks with NodeMCU ESP8266 has been employed. The built-in wifi module of the ESP8266 is utilized for mesh networking which facilitates simultaneous monitoring via multiple nodes in the network. The main goal of the proposed system is to implement a mesh network for simultaneous monitoring which facilitates smart farming.